How to design and evaluate research in education - Fraenkel, Jack R.; Wallen, Norman E.; Hyun, Helen H.
A number of key additions, new illustrations, and improved or refined examples, terminology, and definitions have been incorporated in this edition to further meet the goals of the text. The references have been updated throughout to include the latest research and have been reformatted to reflect use of APA style, research exercises and problem sheets have been revised with more effective questions. The research reports all have newly added margin comments intended to help students apply the text's concepts and also practice evaluating published studies on diverse topics: How manipulatives affect the mathematics achievements in Nigerian schools; 'Belonging means you can go in": children's perspectives and experiences of membership in kindergarten; Students' perceptions of factors influencing their desire to major or not major in science